Nail biopsy: A user's manual - Chander Grover; Shikha Bansal (Wolters Kluwer Medknow Publications, 2018)
Nail biopsy is a procedure not routinely resorted to; but when indicated, it is often the only clue left for diagnosis. At such times, it pays to be conversant with it. It is an investigation that not only provides etiologic, diagnostic, and prognostic information but also aids in understanding the pathogenesis of nail diseases. It can be of therapeutic value, especially with respect to nail tumors. This article compiles the procedural techniques for nail biopsy of various types and attempts to summarize the evidence available in the literature. The objective of nail biopsy is to clinch a precise diagnosis of nail pathology with a simple and safe surgical procedure, avoiding pain or permanent nail damage. Patient selection is of utmost importance, wherein, the patient does not have typical skin lesions, yields inadequate information on routine nail investigations, and has no peripheral vascular compromise. The patient needs to be explained about the risks associated, the expected functional handicap, the time required for regrowth, a possibility of permanent nail dystrophy, and a possibility of not achieving a diagnosis even after the biopsy. Techniques and types of various nail biopsies are being discussed in this article. The specimen could be collected as an excision biopsy, punch biopsy, shave biopsy, or longitudinal biopsy. The trick lies in choosing the appropriate area for biopsy. Various biopsy types discussed in this article include nail plate biopsy (easiest and least scarring); nail bed biopsy (elliptical excision or punch); nail matrix biopsy (elliptical excision, punch excision (≤3 mm) or tangential/shave excision); and nail fold biopsy. Complications reported along with means to minimize them are also discussed.